KOMUNIKASI RITUAL PADA TRADISI PARANG PISANG DI NAGARI SURANTIH, KABUPATEN PESISIR SELATAN, SUMATERA BARAT - Martha, Zike (Universitas Wijaya Kusuma Surabaya, 2020)
The parang pisang tradition is an activity that falls into the category of ritual communication. In this tradition there is a meaning to commemorate the birth of discordant twins so it is believed that there will be no feelings of love for one another. The reseacrh aims to determine the meaning and symbols contained in the parang pisang tradition and the understanding of the younger generation in interpreting this tradition. In this research, information was obtained through 7 (seven) speakers who fit the research criteria. The method used in this research is a qualitative method using syimbolic interactional theory.The results of the study indicate that there are verbal dan non verbal symbols in the tradition of this parang pisang. Verbal symbols in the form of minang rhymes used in the process of communicating during the event. As for non verbal symbols, there are obejcts and equipment used where every object used contains meaning.Kayworld : Tradition, Ritual Communication, Parang Pisang, Nagari Surantih